The influence of English teaching assistant's ICT skills on students' speaking skill / Syarifah Nazurah Abd Khalib - Abd Khalib, Syarifah Nazurah (2014)
Information and Communicative Technology (ICT) has become an important part in the teaching and learning practices at school. For a Native Speaker Teachers (NST), the use of ICT skills in their teaching has helped the students to improve their second language speaking skills. Resulting from that, Malaysia has introduced the English Teaching Assistant (ETA) program since 2006. While speaking skill is seen as among the most important skills in acquiring a second language, ICT skills can help students to motivate and improve their speaking skills. The influence of ICT tools on Malaysian students’ speaking skill is yet to be proven; therefore, this study hopes to see the influence of the ETA’s ICT skill on the students’ speaking skill. 75 students from SMK Kota Masai 2 were given a survey and 4 students were interviewed in order to collect the data for this study. To note, they are the only 75 students taught by the ETA this year and their English lessons are half taught by the ETA and another half is taught by a Malaysian teacher. Classroom observations were also done and the ETA and Malaysian teachers were interviewed. It was found that the ETA’s ICT activities are highly scored by the students as it helps to promote students’ speaking skill. There is also a significance difference in the use of ICT by the ETA and Malaysian Teacher (MT) with computers and search engines being the most used ICT tools and chatting software being the least. It is recommended for future researchers to analyze the impact of ETA ICT skills on other language skills to further understand the use of ICT by ETA in Malaysian classrooms.